DEVELOPMENT OF TECHNOLOGY FOR DRYING AND COMPLETE DRYING OF SILKWORM COCOONS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Primary processing processes using direct and indirect exposure to solar energy on living cocoons have been studied. The technical parameters of an improved device for drying silkworm cocoons, as well as a device for complete drying of cocoons using solar energy, have been determined and a comparison of the experimental results obtained has been considered.